Mathematical modeling of drying kinetics and hygroscopic balance of Cymbopogon flexuosus leaves (Research, Society and Development, 2020)
The Cymbopogon genus is widely studied for its medicinal characteristics, which are recognized and used worldwide. However, there is a need to study the drying kinetics, hygroscopic balance and the color change of Cymbopogon flexuosus leaves by varying the drying temperature. The objective of this work was to study the drying kinetics of Indian grass leaves, to adjust a model among those existing in the literature that best represents the behavior of the sorption isotherm, as well as to analyze the effect of the drying process on the color of the leaves. The Indian grass leaves were cut to a length of 0.2 m and submitted to drying air temperatures of 35, 45, 55 and 70 ºC in a fixed layer mechanical dryer. For the study of the hygroscopic phenomenon, temperatures of 20, 30, 55 and 70 ºC were used with water activities between 10.75 and 85.11%. The model that best represented the drying curves was the Midilli model with an R² of 0.99. The model that best represented the hygroscopic balance curve of Indian grass leaves was that of Modified GAB with R² of 0.94. As the drying air temperature increased, the samples darkened at temperatures above 45 ºC.